The Adverse Effect of Dehumanizing Practices on Student Engagement and Learning in English Language Teaching Classroom - Raju Parajuli (Tribhuvan Journal, 2024)
Knowingly or unknowingly, forgetting our multilingual and multicultural scenario, teachers’ behaviors may create social inequalities and injustices in the classroom; in the name of the dominant language of the school and power relation. Our classroom context is multilingual, multicultural and bilingual where students come from different economic and linguistic background. To some extent, our school system, including textbooks, instruction, curriculum, teaching practices seem to have influenced by the dominant ‘English/Nepali only’ approach. Furthermore, some teachers may not motivate minority students looking their low economic status, uncombed hair, roughly managed shirt-paint, unpolished shoes and low proficiency in English language. In this context, this paper aims to analyze the difficulties and struggle of demotivated (due to teachers’ bias behaviors and friends’ insult upon their appearance and language) Nepali language speaking children’s experiences as they feel insulted in school environment. To fulfill this objective, I adopted narrative research design in line with the qualitative research method. Discussing on the basis of classroom observation and unstructured interviews with the student, this paper analyzes that how the learners are marginalized and forbidden equal access to participate in the mainstream of social and political life that enhances their better learning opportunity and participation in classroom and society to what Bourdieu’s word symbolic violence with some examples of how such social inequalities and injustices are seen in school’s teaching-learning practices. Specially, given the problematic nature of schooling for such learners in some of the schools in Nepal, this paper highlights the need for socially responsive school policies and critical pedagogy, aiming at challenging and changing certain practices having identified a problem; originally propounded by Paulo Freire, a Brazilian educator; understanding the difficulties of living in poverty, local context entertaining the linguistic and cultural diversity of students. This study contributes to all the educational stakeholders to update and change themselves as human- friendly behaviours with the learners that can maintain social equalities and justice.